2020
DOI: 10.3390/membranes10020030
|View full text |Cite
|
Sign up to set email alerts
|

Creating Supported Plasma Membrane Bilayers Using Acoustic Pressure

Abstract: Model membrane systems are essential tools for the study of biological processes in a simplified setting to reveal the underlying physicochemical principles. As cell-derived membrane systems, giant plasma membrane vesicles (GPMVs) constitute an intermediate model between live cells and fully artificial structures. Certain applications, however, require planar membrane surfaces. Here, we report a new approach for creating supported plasma membrane bilayers (SPMBs) by bursting cell-derived GPMVs using ultrasound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To the best of our knowledge, only two different methods have been reported previously to burst pure pdGPMVs to form planar membrane patches on glass substrates. , In both cases, a particular treatment of the surface-adhered pdGPMVs, i.e., an air–water interface compression technique or acoustic radiation forces was required to be able to induce GPMV bursting. Here, we used pdGPMVs and calGPMVs and were able to readily spread them onto oxygen plasma activated SiO 2 surfaces with no additional treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, only two different methods have been reported previously to burst pure pdGPMVs to form planar membrane patches on glass substrates. , In both cases, a particular treatment of the surface-adhered pdGPMVs, i.e., an air–water interface compression technique or acoustic radiation forces was required to be able to induce GPMV bursting. Here, we used pdGPMVs and calGPMVs and were able to readily spread them onto oxygen plasma activated SiO 2 surfaces with no additional treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For supported plasma membranes obtained from pdGPMVs, we obtained diffusion coefficients for R18 of D = 1.0 ± 0.8 μm 2 /s (n = 17), similar to what has been reported in literature. 25,26 Supported plasma membranes derived from calGPMVs show by a factor of 2.5 lower average diffusion coefficient of D = 0.4 ± 0.1 μm 2 /s (n = 16). Interestingly, already the diffusion coefficients of R18 in GPMVs differ dependent on the vesiculation agents.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without doubt, having such valuable tools will allow us to study the effect of checkpoint inhibitors and immune stimulators at a physiological level previously unmatched by synthetic systems alone. For this purpose, the exploitation of native membrane systems such as giant PM vesicles [164] and their adaptation into supported PM bilayers [165] is a mandatory step to unravel the fundamental dynamics of membrane physiology for different phenotypical states.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Sezgin et al [5] reported a novel approach for creating supported plasma membrane bilayers (SPMBs) by bursting cell-derived giant plasma membrane vesicles using an ultrasound microfluidic device. Sezgin et al showed that the diffusion of lipids as well as proteins in these SPMBs in the outer leaflet is preserved, suggesting that these molecules are accessible on the surface of the bilayers.…”
mentioning
confidence: 99%